Does economic condition matter?: Citizenship activity of young people in countries with different economic status. Issue 2 (1st June 2017) - Krzywosz-Rynkiewicz, Beata; Zalewska, Anna M.; Skład, Marcin
The relationship between citizenship activity and economic status is examined and discussed in the article. We refer to the three-dimensional citizenship model by Zalewska and Krzywosz-Rynkiewicz: passive (patriotism and national activity), semi-active (loyalty and civic virtues) and active (political, social personal and action for change). A total of 4920 students aged 11–12, 14–15 and 17–18 years from fourteen European countries were examined using the Citizenship Behavior Questionnaire. The results indicate that economic growth is linked to various forms of citizenship behaviours. The wealth and social development of a country are negatively correlated with passive and active citizenship, which is higher in lessdeveloped states. The rate of economic growth and citizenship activity is bound by a curvilinear relationship. In countries with moderate rates of wealth accumulation, the levels of all forms of citizenship are significantly lower than those in countries with the lowest and highest rates of economic growth. The level of citizenship activity varies according to the level of social inequality: in the most stratified countries, citizenship activity is significantly higher than in countries with moderate and low levels of inequality, which do not differ from one another. Similar correlations are noted for passive and active citizenship. Only semi-active citizenship is lowest in countries with moderate levels of inequality.